Megaclasts in geoconservation: sedimentological questions, anthropogenic influence, and geotourism potential - Lubova, Katrin A.; Zayats, Pavel P.; Ruban, Dmitry A.; Tiess, Günter (Geologos, 2014)
Megaclasts are sedimentary particles larger than boulders. Their huge size and scattered occurrence make them objects that deserve geological heritage, requiring conservation. Investigation of megaclasts for the purpose faces difficulties because of the distinction between boulders and megaclasts. Local study of Quaternary large stones in Mountainous Adygeja (W Caucasus, SW Russia) suggests 2 m as a suitable size criterion, although only locally. Shape, occurrence, and origin of megaclasts require additional attention. Geoconservation may result in anthropogenic disturbances of the natural landscape through removal of vegetation, access constructions, and restoration. The geotourism potential of megaclasts is partly determined by their huge size and their rare and scattered occurrence. Aesthetic qualities, local legends, and co-occurrence with prehistoric megalithic constructions increase this potential. The Maiden’s Stone in Mountainous Adygeja, which is 35 m long, has been a tourist attraction already for decades. It is an impressive example of geoconconservation and geotourism connected with megaclasts. Generally, megaclasts increase the value (including the scientific importance) of the geological heritage of Mountainous Adygeja, where a geopark might be established.